Peran Teknologi Internet Dalam E-Commerce - Sukma Nugraha; Dini Nuraeni (Institut Pendidikan Indonesia, 2021)
This study discusses the role of internet technology in e-commerce. This study uses a causal research design on 58 respondents. The data technique used is simple linear regression with SPSS 21 application. Technology plays a role in the development of e-commerce. This shows that customers will be satisfied if they use technology that offers good technology, low risk and the development of e-commerce. This research has benefits in developing an applied theory that information technology plays a significant role in e-commerce. For further research, it is expected to examine the dividend variable that is not listed in this research model. This research has practical benefits for business actors who use e-commerce to improve marketing performance by always paying attention to the role of information technology in e-commerce